Karel Vrijman : wederwaardigheden en wilskracht van een dorpsonderwijzer. Schetsen uit het werkelijk leven - Voorlichter, K.L.; Waerseggers, P.J. (Gent : W. Rogghé, 1879)
Bibliotheek E. Anseele
Nederlands
Monografie
Keywords: Vrijman, Karel